Modulation of autophagy as a therapeutic strategy for Toxoplasma gondii infection - Cheng, Ao; Zhang, Huanan; Chen, Baike; Zheng, Shengyao; Wang, Hongyi; Shi, Yijia; You, Siyao; Li, Ming; Jiang, Liping (Frontiers in Cellular and Infection Microbiology, 2022)
Toxoplasma gondii infection is a severe health threat that endangers billions of people worldwide. T. gondii utilizes the host cell membrane to form a parasitophorous vacuole (PV), thereby fully isolating itself from the host cell cytoplasm and making intracellular clearance difficult. PV can be targeted and destroyed by autophagy. Autophagic targeting results in T. gondii killing via the fusion of autophagosomes and lysosomes. However, T. gondii has developed many strategies to suppress autophagic targeting. Accordingly, the interplay between host cell autophagy and T. gondii is an emerging area with important practical implications. By promoting the canonical autophagy pathway or attenuating the suppression of autophagic targeting, autophagy can be effectively utilized in the development of novel therapeutic strategies against T gondii. Here, we have illustrated the complex interplay between host cell mediated autophagy and T. gondii. Different strategies to promote autophagy in order to target the parasite have been elucidated. Besides, we have analyzed some potential new drug molecules from the DrugBank database using bioinformatics tools, which can modulate autophagy. Various challenges and opportunities focusing autophagy mediated T. gondii clearance have been discussed, which will provide new insights for the development of novel drugs against the parasite.